2010
DOI: 10.2174/1877729501002010024
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Surface Roughness Effects on Nucleate Boiling Heat Transfer~!2009-10-31~!2010-01-01~!2010-04-16~!

Abstract: Abstract:The paper aims at an overview of heating surface microstructure effects on nucleate boiling heat transfer. A comprehensive chronological literature survey is presented followed by an analysis of the results of an experimental investigation. Boiling data of refrigerants R-134a and R-123 on 19 mm diameter copper and brass tubes of average surface roughness varying from 0.07 μm to 10.5 μm have been gathered under the present investigation. Though most of the data confirm previous literature trends, accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…It can be quickly seen that the highest performance is reserved for the 10:1 aspect ratio. These results correlate well with the results of Jabardo [86] who found that the heat transfer coefficient and heat flux increases and then decreases with increasing surface roughness.…”
Section: Effect Of Aspect Ratio/heightsupporting
confidence: 91%
“…It can be quickly seen that the highest performance is reserved for the 10:1 aspect ratio. These results correlate well with the results of Jabardo [86] who found that the heat transfer coefficient and heat flux increases and then decreases with increasing surface roughness.…”
Section: Effect Of Aspect Ratio/heightsupporting
confidence: 91%
“…These variances are partially due to the different methods used for the surface preparation [10] and the different properties of the surface materials [9,11]. Some studies have indicated that the enhancement in nucleate boiling increases with increasing surface roughness up to a point, beyond which little changes occur [12]. Other investigators have reported that increasing surface roughness increases its hydrophobicity [13][14][15], decreasing the bubble departure diameter and increasing the detachment frequency, and thus enhancing nucleate boiling.…”
Section: Introductionmentioning
confidence: 99%
“…A different way to obtain was proposed in [17], where it was expressed as a function of the roughness arithmetic average as:…”
Section: Volume-of-fluid (Vof) Modelmentioning
confidence: 99%
“…The fluid/surface material combinations are accounted for by coefficient , whose values are around 1, ranging from 0.8 to 1.3 [17]. Even if the fluids are different from that considered in this work, the possibility of applying equation (5) to the present case was checked.…”
Section: Volume-of-fluid (Vof) Modelmentioning
confidence: 99%